QUALITY OF WORKING LIFE OF EMPLOYEES IN ROJANA INDUSTRIAL GROUP AYUTTHAYA - เนาว์วัน วันทนา (Journal of MCU Social Science Review, 2018)
This research aims to study the quality of working life of employees of Rojana Industrial Group, PhraNakhon Si Ayutthaya Province and analysis of factors related to work affecting the quality of working life of employees of Rojana Industrial Group, PhraNakhon Si Ayutthaya Province, and to present a model for improving the quality of working life of employees in Rojana Industrial Group, PhraNakhon Si Ayutthaya Province. Methodology was the mixed methods between qualitative and quantitative research. The samplings were Rojana industrial employees 400 people in Ayutthaya Province. The instruments used in this research were questionnaires and in-depth interviews. Data were analyzed by means of frequency, mean and standard deviation, One-Way ANOVA Analysis and Pearson Correlation (Pearson Correlation). The results showed that the totally quality of working life of employees was high level, Engagement Its mean was 3.52 Development of operational knowledge Secondly, adequate and fair remuneration Its mean was 3.50 and the smallest is the rewarding and fair. The balance between life and work, factors related to overall work performance was high level were the variety of tasks. The greatest sharing of knowledge in working together was the motivation to work was higher Its mean was 3.58 In terms of good relationships with colleagues Its mean was 3.56 and the least is the chance to recognize the performance. Reporting results and performance recommendations if there is an error Its mean was 3.38. The results of comparative analysis, educational attainment, and challenging job opportunities found that knowledge can be found that employees with high school / vocational education and staff with education / diplomas. There were different job opportunities, different skill competencies (Sig = 0.032), and employees with undergraduate education. There are different opportunities for performance challenges (Sig = 0.000). At the end of the Diploma / Diploma, and staff are level with a bachelor’s degree. There were different job opportunities, different skill competencies (Sig = 0.015). The model for development of the quality of working life of the employees was found to be the most rewarding and fair, secondly, security and career advancement opportunities. Safety and hygiene Minimal in terms of rules and regulations in the work. By way of developing employee training, positive thinking. In practice Performance standards from external and internal trainers. Health promotion activities and there is harmony and other benefits to motivation. And the appropriate compensation for the job.